2015
DOI: 10.1002/pbc.25641
|View full text |Cite
|
Sign up to set email alerts
|

Inferior vena cava (IVC) filters in children: A 10‐year single center experience

Abstract: Although in most cases, IVC filters were placed for prophylactic indications, the evidence to support their role in this setting is limited. Their low retrieval rate and high filter-related complication rate question their extensive utilization in children. Dedicated follow-up is necessary to detect complications and to ensure that an attempt at retrieval is made when feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…A single-center retrospective study of IVC filters in children found there were no complications related to deployment, indicating that the procedure is, at the very least, safe in this population. However, in this study, 10% of patients failed to have their filters retrieved, 13 which may have significant long-term implications. Another population that requires special attention is pregnant patients.…”
Section: Special Populationsmentioning
confidence: 70%
See 1 more Smart Citation
“…A single-center retrospective study of IVC filters in children found there were no complications related to deployment, indicating that the procedure is, at the very least, safe in this population. However, in this study, 10% of patients failed to have their filters retrieved, 13 which may have significant long-term implications. Another population that requires special attention is pregnant patients.…”
Section: Special Populationsmentioning
confidence: 70%
“…Although IVC filters are used in children, recommendations for their use are based largely on adult trials; recommendations in the pediatric literature are limited to retrospective studies and case reports. 13,14 Current guidelines vary based on specific medical societies: the American College of Chest Physicians recommends filter use in patients weighing at least 10 kg and with known acute DVT and contraindication to anticoagulation, the American Heart Association includes use in recurrent DVT, and the Society of Interventional Radiology includes a recommendation for prophylactic use in high-risk populations. 14 The unique concern for patient (and IVC) growth and for greater expected survival in these patients should give the clinician pause when considering IVC filter placement over mechanical, pharmacologic, or other alternative therapies.…”
Section: Special Populationsmentioning
confidence: 99%
“…Retrievable IVC filters have been recommended in patients >10 kg with lower extremity deep venous thrombosis and contraindication to or failure of anticoagulation 9 . Indications for their use tend to vary between different institutions 9,11,12 . There has been a trend for their use as prophylaxis after trauma, as well as in the treatment of VTE 13 .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the placement of filters in the superior vena cava has been shown to be effective and safe, using the filters originally designed for the inferior vena cava. 2 In paediatric patients, several small single centre reports [3][4][5] showed that the use of filters in the inferior vena cava is feasible and effective, although concerns were raised regarding the potential risk for complications, such as vena cava perforation. 4…”
mentioning
confidence: 99%
“…2 In paediatric patients, several small single centre reports [3][4][5] showed that the use of filters in the inferior vena cava is feasible and effective, although concerns were raised regarding the potential risk for complications, such as vena cava perforation. 4…”
mentioning
confidence: 99%